Celebrating 'Lilburn 100' at Massey University library Wellington campus - Smith E; Hoskins R (International Association of Music Libraries, New Zealand Branch)
Reports on the 'Lilburn 100' centenary exhibition held at Massey Library, Wellington Campus from 27 Oct to 20 Nov 2015. Includes reflections by Massey Associate Professor Robert Hoskins on publishing Lilburn's music.
Keywords: Music -- Exhibitions; Lilburn, Douglas 1915-2001